Clinical and imaging outcomes over 12 weeks in elite athletes with early-stage tendinopathy - Meulengracht, C. S.; Seidler, M.; Svensson, R. B.; Kracht, M.; Zeidan, A.; Christensen, K. Ø.; Jensen, M. H. H.; Hansen, P.; Boesen, M.; Brushøj, C.; Magnusson, S. P.; Bahr, R.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Knowledge of how to treat chronic tendinopathy has advanced in recent years, but the treatment of early tendinopathy is not well understood. The main purpose of this prospective observational study was to investigate if changes occur in clinical and imaging outcomes over 12 weeks in elite athletes with recent debut of tendinopathy. Sixty-five elite adult athletes (24 ± 5 years) with early Achilles or patellar tendinopathy (symptoms < 3 months) were examined at baseline and after 12 weeks. Patients were divided into groups based on the duration of symptoms at the time of inclusion: (T1): 0-1 month, (T2): 1-2 months, or (T3): 2-3 months. Pain-guided activity modification was the only intervention. We assessed the following clinical outcomes: Questionnaires (Victorian Institute of Sports Assessment (VISA)) and pain scores (0-10 numeric rating scale, NRS), structural outcomes from ultrasonography: Thickness, echogenicity, and Doppler flow, and from magnetic resonance imaging: Cross-sectional area (CSA), thickness and length. Tendinopathic Achilles and patellar tendons displayed no significant differences on imaging tendon structural outcomes between T1 (n = 19), T2 (n = 23), and T3 (n = 20) at baseline or after 12 weeks, with one exception: Patellar tendons in T1 were thicker than T2 and T3 at baseline. Although athletes improved clinically on VISA and most NRS scores after 12 weeks, affected tendons with greater thickness, CSA and Doppler flow than contralateral tendons at baseline remained unchanged after 12 weeks. In conclusion, these data suggest that early tendinopathy in elite athletes can improve clinically after 12 weeks while morphology remains unchanged.